Hipótese sacrificial - António Pedro Dores (e-cadernos ces)
Why do prison studies not explain notorious phenomena such as institutional violence in the most secure places in the world, the very different criminalization of sexes and social classes, the declared and unfulfilled intentions of states of respect of human rights? Why, in this regard, do ideological prejudices dominate? Prison sentences are modern phenomena, alongside wage labor. Prison and capitalism abolitionisms have separate histories. What they have in common is that they were both recovered by the system, and are now out of the game. Prison secrets are accompanied by other cognitive black holes, such as the social need to organize human sacrifices, both in penitentiaries and at work. Including the sacrificial economy in the analysis can help to overcome current epistemic limitations.